Performance of loose sand with different waste materials in stone columns in North Cyprus. Issue 5 (24th May 2019) - Alnunu, Mahdi Z; Nalbantoglu, Zalihe
Abstract : Stone columns are used to enhance the bearing capacity of poor ground and reduce the compressibility of soft clays. The aim of this study is to evaluate the effectiveness of stone columns with different waste materials on the performance of loose sand in North Cyprus. The study provides guidelines for the selection of the most effective and economical material for stone column construction. In this study, waste materials from different construction sites were selected: shredded bricks, crushed waste stone and crushed old concrete. The stone columns were constructed with these waste materials. Load–settlement responses of the unreinforced and reinforced soils with a single stone column and a group of stone columns constructed with these waste materials were determined under the same loading conditions. The obtained results showed a very good improvement in the settlement behaviour of the loose sand. As a conclusion, local waste building materials can be used effectively for stone column construction. The use of these waste materials will contribute to recycling and environmental sustainability.